CC-Human Menopausal Gonadotropin Combined with Growth Hormone in Mini-stimulation Protocol could Improve Clinical Outcome in Poor Ovarian Responders - Polim, Arie A; Sini, Ivan R; Anwar, Indra NC; Pradana, Aryando; Kurniawati, Kurniawati; Fani, Erliana (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To investigate the role of CC-highly purified Human Menopausal Gonadotropin (hpHMG) and Growth Hormone (GH) in mini-stimulation protocol to improve outcome in poor ovarian responders (POR). Method: All patients were given clomiphene citrate 150 mg from day 3 to day 7 of menstrual cycle followed by 150 IU hpHMG daily from day 8 until ovulation trigger. Two groups were observed where one group received GH and the other arm did not. In the GH group, 8 IU of GH were given from day 1 of stimulation until stimulation was stopped. GnRH antagonist was used to suppress ovulation. Result: Among 51 eligible women, 29 patients with GH and 22 patients without GH, no difference was observed in the number of oocytes retrieved (2.21 versus 2.64) and the number of embryos transferred (1.24 versus 1.68) in the GH group versus the group without GH, respectively. Total clinical pregnancy rate was 17.6%. No significant difference in pregnancy and ongoing pregnancy rate in both groups (17.2% versus 18.2%) and (13.8% versus 13.6%), respectively. In patients older than 40 years old, GH showed a 4-fold likelihood in producing top quality embryos (44.8% vs 13.6%, OR=3.6, p=0.05). Conclusion: CC-HMG regimen in mini-stimulation protocol is an effective option in poor responders. Additional GH in ministimulation program provided a higher number of top quality embryos in women older than 40 years old, although there were no difference in clinical or ongoing pregnancy rate. Keywords: CC-HMG, growth hormone, IVF, mini-stimulation protocol, poor ovarian responders